Temporal dynamics of light-written waveguides in unbiased liquid crystals - Alberucci, Alessandro; Barboza, Raouf; Jisha, Chandroth P.; Nolte, Stefan (Journal of the Optical Society of America B-Optical Physics, 2018)
The control of light by light is one of the main aims in modern photonics. In this context, a fundamental cornerstone is the realization of light-written waveguides in real time, resulting in all-optical reconfigurability of communication networks. Light-written waveguides are often associated with spatial solitons, that is, non-diffracting waves due to a nonlinear self-focusing effect in the harmonic regime. From an applicative point of view, it is important to establish the temporal dynamics for the formation of such light-written guides. Here, we investigate theoretically the temporal dynamics in nematic liquid crystals, a material where spatial solitons can be induced using continuous wave lasers with a few milliwatts of power. We fully address the role of the spatial walk-off and the longitudinal nonlocality in the waveguide formation. We show that for powers large enough to induce light self-steering the beam undergoes several fluctuations before reaching the stationary regime, in turn leading to a much longer formation time for the light-written waveguide.
CRIS-Team Scopus Importer:2023-04-20